Clinical profile and quality of life in myasthenia gravis using MGQOL15 R(Hindi): An Indian perspective - Ganeshgouda Majigoudra; Ashish K Duggal; Debashish Chowdhury; Arun Koul; Vineet K Todi; Sujata Roshan (Annals of Indian Academy of Neurology, 2023)
Background: Myasthenia Gravis (MG) is a chronic fluctuating illness, due to the dysfunction of neuromuscular junction which is autoimmune in nature. The disease severely affects the Quality Of Life (QOL). Objective: The primary objective of our study was to assess the QOL in patients with MG using Short Form 36 (SF 36) and MGQOL 15 R (Hindi translated).The secondary objective was to assess the correlation of age, sex, illness duration, clinical characteristics, severity, and treatment with the QOL in MG patients. Methodology: A cross sectional study of 55 MG patients was done to analyse and evaluate the clinical status using Hybrid Myasthenia Gravis Foundation of America (HMGFA), Myasthenia gravis composite score (MGCS) and The Myasthenia Gravis Activities of Daily Living (MG – ADL). QOL was assessed by SF 36 and Hindi version of Myasthenia Gravis Quality of Life 15 – Revised (MG-QOL15R) score. Results: 78.2% patients had generalized MG. The mean MGC and MG-ADL scores were 5.27 and 3.29 (95% CI: 2.24 -4.34) respectively. The mean MGQOL15R score was 6.52 ± 7.7 and the score correlated with the symptoms. The SF 36 scores were the best and the worst in the bodily pain (93.72 ± 13.52) and general health subset (61.81 ± 39.64) respectively. Except for steroid dose, there was no significant correlation between SF36 and other factors. Conclusion: QOL in MG was found to be affected due to the disease. The MGQOL 15 R scores correlated with the clinical features, remission or active status, steroid use and thymectomy. No Significant association was observed between MG QOL scores and various lab parameters and repetitive nerve stimulation (RNS) test results. Higher dose of steroid was associated with poor QOL, while thymectomy was associated with better QOL scores. MGQOL15R (Hindi) is a quick and simple tool to assess the QOL in MG patients.